The Political Economy of Corporate Social Responsibility in the Resources Sector in Western Australia: A case study of the proposed James Price Point LNG precinct - Wesley, Anthea; MacCallum, Diana (Springer Verlag, 2014)
Over the last few years, there has been increased emphasis placed on the “right way” of doing business involving transparent and ethical interactions with communities of interest. The global resource industry is regarded as the one of the primary champions and leaders of this corporate social responsibility (CSR) movement. Increasingly, however, its credibility within the industry is being challenged by the existence of conflict and confrontation and accusations of company misdemeanours that can surround resource development projects globally. For Western Australia’s resource sector, the liquefied natural gas precinct recently proposed at James Price Point in the Kimberley is a prime example. The aim of this chapter is to take a critical assessment of the relations and practices that define interactions between industry, government and community spheres, as a way to make sense of the conflict that surrounds this project. The analysis is informed by theories of governmentality and spatiality, which captures the ‘spaces of CSR’ framework discussed in this chapter. The argument is presented that resource development projects in Western Australia are shaped and defined by a series of historical, political, institutional, economic and social forces, prevailing values and assumptions and also relations of power. This is shown to play out in the contest surrounding the LNG precinct. As a consequence, the practice of CSR in the resource industry is shown to be more complex, problematic and dynamic than is suggested within broader CSR scholarship.